A Cyclic Peptide Epitope of an Under-Explored VEGF-B Loop 1 Demonstrated In Vivo Anti-Angiogenic and Anti-Tumor Activities - Wang, Lei; Xu, Meng; Hu, Haofeng; Zhang, Lun; Ye, Fei; Jin, Jia; Fang, Hongming; Chen, Jian; Chen, Guiqian; Broussy, Sylvain; Vidal, Michel; Lv, Zhengbing; et al. (Frontiers in Pharmacology, 2021)
Pathological angiogenesis is mainly initiated by the binding of abnormal expressed vascular endothelial growth factors (VEGFs) to their receptors (VEGFRs). Blocking the VEGF/VEGFR interaction is a clinically proven treatment in cancer. Our previous work by epitope scan had identified cyclic peptides, mimicking the loop 1 of VEGF-A, VEGF-B and placental growth factor (PlGF), inhibited effectively the VEGF/VEGFR interaction in ELISA. We described here the docking study of these peptides on VEGFR1 to identify their binding sites. The cellular anti-angiogenic activities were examined by inhibition of VEGF-A induced cell proliferation, migration and tube formation in human umbilical vein endothelial cells (HUVECs). The ability of these peptides to inhibit MAPK/ERK1/2 signaling pathway was examined as well. On chick embryo chorioallantoic membrane (CAM) model, a cyclic peptide named B-cL1 with most potent in vitro activity showed important in vivo anti-angiogenic effect. Finally, B-cL1 inhibited VEGF induced human gastric cancer SGC-7901 cells proliferation. It showed anti-tumoral effect on SGC-7901 xenografted BALB/c nude mouse model. The cyclic peptides B-cL1 constitutes an anti-angiogenic peptide drug lead for the design of new and more potent VEGFR antagonists in the treatment of angiogenesis related diseases.